Development Of A System For Measuring Pedal Force In Arm Leg Pedal Exercise - Najib, Mohammad Amirul Akmal Mohd (Universiti Sains Malaysia, 2021)
Nowadays, stroke issues become important field which many researchers and scientist have work on how to get the best method for their recovery. For stroke patients, the most popular method to recover is through aerobic exercise like walking, cycling, or running. Rehabilitation cycle have been used in medication field for the hemiparesis patients. Current designs do not provide no feedback system to the patient. It is difficult to determine whether the patient perform effectively. The problem that occurs during the therapy is time consuming because only single limbs were treated at one time. The purpose of this study is to determine the parameters for both active and passive mode and the effectiveness of feedback system to the stroke patients during the therapy. At the end experiment the active and passive activity for both upper and lower limb in term of angular speed, angular acceleration, speed and acceleration have been study. From the result it can be shown that the average of angular speed, angular acceleration, speed and acceleration, the lowest are active disengage at upper limb with -0.18482 deg/s, active engage at lower limb with -0.37149 deg/s2 and passive engage activity at upper limb which is 0.127865 m/s and -8.2759E-05 m/s2 respectively. To see the significant of active and passive activities, the T-test with 95% confidence interval was conducted. The results are only speed for both limbs have significant difference while others have no significant value. From this study, it can be clearly observed that active and passive activity almost have same effect. So, the severe stroke patients can do the passive mode exercise with have almost same effect as active mode before they can move their own limbs. The feedback system to detect the force difference that too large have been shown in the result part. The figure show that when the force difference is too large which the fraction of difference and total force value exceed 0.4 or -0.4, the LED will start to be blinking until the force difference become stable. The T-test with 95% confidence interval was conducted between both legs at active and passive mode. It shows that there were significant different for both active and passive mode. So, the feedback system can notify the user if force difference is too big where they will be improving force between both legs.